2009
DOI: 10.1093/cercor/bhp198
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Anatomy in Autism Spectrum Disorder: An In Vivo MRI Study on the Effect of Age

Abstract: There is increasing evidence that children with autism spectrum disorder (ASD) have age-related differences from controls in cortical volume (CV). It is less clear, however, if these persist in adulthood and whether these reflect alterations in cortical thickness (CT) or cortical surface area (SA). Hence, we used magnetic resonance imaging to investigate the relationship between age and CV, CT, and SA in 127 males aged 10 through 60 years (76 with ASD and 51 healthy controls). "Regional" analyses (using cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
161
5
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(200 citation statements)
references
References 52 publications
29
161
5
5
Order By: Relevance
“…To date, few studies have investigated age-related changes in cortical thickness in individuals with ASD and collectively they suggest a complex pattern of cortical thickness maturation in this group. In agreement with the current findings, studies that included participants across a wide age range (Raznahan et al, 2010;Scheel et al, 2011) found more regions with little to no change in cortical thickness in individuals with ASD. In comparison, studies with narrower age ranges report that the cortex thins with age in individuals with ASD.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…To date, few studies have investigated age-related changes in cortical thickness in individuals with ASD and collectively they suggest a complex pattern of cortical thickness maturation in this group. In agreement with the current findings, studies that included participants across a wide age range (Raznahan et al, 2010;Scheel et al, 2011) found more regions with little to no change in cortical thickness in individuals with ASD. In comparison, studies with narrower age ranges report that the cortex thins with age in individuals with ASD.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, no longitudinal studies in individuals with ASD have examined cortical thickness development across a wide age-range. Cross-sectional studies in ASD suggest atypical cortical thickness changes between childhood and adulthood in individuals with ASD (Mak-Fan, Taylor, Roberts, & Raznahan et al, 2010;Scheel et al, 2011;Wallace, Dankner, Kenworthy, Giedd, & Martin, 2010). In children with ASD aged 6-15 years, Mak-Fan et al (2011) reported decreased cortical thickness with age across the entire brain, as well as in the frontal and parietal lobes; however group differences were not found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that imaging findings in autism often are not robust because of the inherent heterogeneity of the autism spectrum and small sample sizes, this study's multiparameter classifier should demonstrate high levels of sensitivity with additional samples of autistic participants that vary in age and autistic characteristics. In many of the frontal, temporal, and parietal regions identified by the Ecker et al (2010b) classifier, Raznahan et al (2010) found that younger autistic participants tend to have lower cortical thickness and older autistic participants tend to have greater cortical thickness compared with nonautistic participants. The role of age in autistic and non-autistic differences in cortical thickness complicates the replicability of the Ecker et al (2010b) classifier with younger samples.…”
mentioning
confidence: 96%
“…The extraction of appropriate features for brain classification is an essential, yet challenging research area. Recent neuropathological studies show an increasing evidence that children diagnosed with autism spectrum disorder have anatomical differences from controls in cortical volume (CV) [59]. Another study [60] observed differences between the autism and control subjects in total gray matter volumes over time with significantly greater decreases in the autism group compared with control subjects, in addition to the differences in cortical thickness (CT) over time with decreases in the autism group compared with control subjects in several brain regions including the frontal lobe.…”
Section: B Computer-aided Diagnosis (Cad) System For Autism Diagnosismentioning
confidence: 99%